Nursing Intervention in Overcoming Decreased Cardiac Output in Patients with a Medical Diagnosis of Inappropriate Sinus Tachycardia (IST) in the CICU Room "Case Study" - Widya Nurwulan Santika Utami; Donny Nurhamsyah; Aan Nur'aeni (Padjadjaran Acute Care Nursing Journal, 2022)
Inappropriate Sinus Tachycardia (IST), which is a condition in which a person has a heart rate of more than 100 beats per minute for no apparent reason and if left untreated it will last for months or even years. Inappropriate sinus tachycardia can cause myocardial ischemia, reduce ventricular filling time, cause decreased cardiac output, cardiomyopathy, cardiac arrest, and death. in Indonesia itself there are no studies on IST so that researchers are interested in explaining interventions that can be done to reduce discomfort in IST patients.This research uses case studies. A 30 year old woman came to the hospital with complaints of palpitations, dyspnea, nausea and vomiting. Patients are given bed rest management, hemodynamic monitoring (vital signs, lab electrolytes, EKG), administration of oxygen, deep breathing relaxation for 3 days with a duration of 10 minutes.The results of the study found complaints of chest palpitations in patients resolved with HR: 60x/minute, BP: 98/86 mmHg, RR: 17x/minute, SpO2: 99%, complaints of nausea, vomiting and tightness in patients resolved and on the last day obtained Electrolyte test results were within normal limits.The patient was given non-pharmacological therapy, namely deep breathing relaxation therapy with the result that the patient experienced a decrease in heart rate and an increase in oxygen saturation. Giving deep breathing relaxation techniques will automatically stimulate the sympathetic nervous system to reduce levels of catecholamine substances, causing blood vessels to dilate and eventually blood pressure, heart rate, respiratory rate decrease.